Effect of plumage colour on carcass characteristics and meat quality of Nigeria local turkeys - Yusuff, A.T.; Saheed, K.R.; Badmos, A.A.; DeCampos, J.S.; Aremu, J.O. (Nigerian Journal of Animal Science, 2001)
This study examined the effect of plumage colour on carcass characteristics and meat quality of Nigeria local turkeys. Nine 14weeks local turkeys of different plumage colour (3 blacks, 3 white, and 3 mixed colour) were studied during the experiment. The birds were allotted into treatments based on the 3 plumage colours. Data taken were carcass weight, dressing percentage, prime cuts and relative organs’ weights, pH, drip loss, cook loss, meat colour and sensory attributes of cooked meat. Data collected were subjected to analysis of variance using SPSS version 25. The result obtained revealed that plumage colour affects the pH of turkey meat with a significantly higher carcass pH (5.68) from the mixed colour plumage group. It was also noted that, carcass weight, prime cuts and relative organ weight showed no significant difference (P > 0.05) irrespective of plumage colours. Similarly, the drip loss, cook loss and meat colour (lightness, redness and yellowness) were not influenced by plumage colour of the turkey while the sensory evaluation revealed that black plumaged birds group were more juicy, and had the best aroma and overall acceptability compared to others. It is therefore concluded that plumage colour affects the pH and juiciness, aroma and overall acceptability of Nigeria local turkey meat